PENGARUH PROGRAM PENGEMBANGAN PENDIDIKAN AGAMA ISLAM (PPAI) TERHADAP AKHLAK SISWA DI SMK BAKTI NUSANTARA 666 BANDUNG - Iqbal Maulana Yusup (Al-Mau'izhoh, 2020)
This study aims to uncover the reality of the PPAI program (Development of PAI), the reality of student morals, and the effect of the PPAI program on student morals at SMK Bakti Nusantara 666. This research was conducted at the Bakti Nusantara Vocational High School (SMK) Bandung, Indonesia, using a quantitative approach correlative descriptive method. Primary data in this study are: Principal, Islamic Religious Education Development Teacher (PPAI), and Students. Secondary data is data collected by researchers as a support from the first source. Data processing is done by editing, Scoring, and the distribution of questionnaires that are processed by statistics, namely by using the relative frequency distribution table. Research results show, first, the PPAI program has been implemented significantly, in accordance with established procedures; secondly, the morals of students are good, the PPAI program has been implemented in daily life; third, the PPAI program has a significant effect on the morals of students of SMK Bakti Nusantara 666 Bandung.